(untitled) (Journal of Parents and Teachers, 2025)
The article highlights the transformative role of youth leadership in education. Young people not only question traditional models but also drive change through active participation, innovation, and community work. Through networks like Fe y Alegría’s Generación 21+, they strengthen skills, create social projects, and foster resilience. Despite challenges such as lack of resources and cultural barriers, youth leadership helps build more just and inclusive societies, acting as agents of change both now and in the future.